The Role of T Cell Senescence in Neurological Diseases and Its Regulation by Cellular Metabolism - Fessler, Johannes; Angiari, Stefano (Frontiers in Immunology, 2021)
Immunosenescence is a state of dysregulated leukocyte function characterised by arrested cell cycle, telomere shortening, expression of markers of cellular stress, and secretion of pro-inflammatory mediators. Immunosenescence principally develops during aging, but it may also be induced in other pathological settings, such as chronic viral infections and autoimmune diseases. Appearance of senescent immune cells has been shown to potentially cause chronic inflammation and tissue damage, suggesting an important role for this process in organismal homeostasis. In particular, the presence of senescent T lymphocytes has been reported in neurological diseases, with some works pointing towards a direct connection between T cell senescence, inflammation and neuronal damage. In this minireview, we provide an overview on the role of T cell senescence in neurological disorders, in particular in multiple sclerosis and Alzheimer disease. We also discuss recent literature investigating how metabolic remodelling controls the development of a senescence phenotype in T cells. Targeting metabolic pathways involved in the induction of senescent T cells may indeed represent a novel approach to limit their inflammatory activity and prevent neuroinflammation and neurodegeneration.